The worn tyres pyrolisis’ solid products opportunity application as fuel substitute assessment - Pozdnyakova, Olena; Vnykova, Nataliia (Lviv Politechnic Publishing House, 2017)
It has been shown that, without additional processing pyrolysis products of tyres cannot be used in practice. The mixture of pellets-pyrolysis char-coal have been proposed as an alternative fuel for energy plants.
Keywords: end of life tyres; char; pyrolys